2018
DOI: 10.3390/bioengineering5020031
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Model Development of the Elbow Joint with an Experimental Evaluation

Abstract: A dynamic musculoskeletal model of the elbow joint in which muscle, ligament, and articular surface contact forces are predicted concurrently would be an ideal tool for patient-specific preoperative planning, computer-aided surgery, and rehabilitation. Existing musculoskeletal elbow joint models have limited clinical applicability because of idealizing the elbow as a mechanical hinge joint or ignoring important soft tissue (e.g., cartilage) contributions. The purpose of this study was to develop a subject-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Elbow flexor and extensor muscles, together with the joint articulation, could also indirectly affect the mechanical resistance of the external valgus torque at the elbow during pitching (Van Trigt et al, 2021 ). In-vitro cadaver studies and forward dynamic model studies showed that the biceps and triceps are important in stabilizing the elbow joint (Morrey et al, 1991 ; Seiber et al, 2009 ; Rahman et al, 2018 ). Our results show co-contraction of elbow flexors and extensors at the instant of MER during fastball pitching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbow flexor and extensor muscles, together with the joint articulation, could also indirectly affect the mechanical resistance of the external valgus torque at the elbow during pitching (Van Trigt et al, 2021 ). In-vitro cadaver studies and forward dynamic model studies showed that the biceps and triceps are important in stabilizing the elbow joint (Morrey et al, 1991 ; Seiber et al, 2009 ; Rahman et al, 2018 ). Our results show co-contraction of elbow flexors and extensors at the instant of MER during fastball pitching.…”
Section: Discussionmentioning
confidence: 99%
“…Several in-vitro studies showed that simulated loading of the biceps and triceps brachii significantly decreased the ulnohumeral joint space and thus resist the external valgus torque (Morrey et al, 1991 ; Seiber et al, 2009 ). In addition, a forward dynamic musculoskeletal model showed that simulated activation of the triceps brachii and biceps brachii increased joint contact force (Rahman et al, 2018 ). We therefore assume that co-contraction of flexor and extensor elbow muscles could indirectly counteract the external valgus torque indicating an indirect effect.…”
Section: Introductionmentioning
confidence: 99%
“…A common approach here is to employ single or multiple line segments connecting bones (see e.g. for the knee [9,10], forearm [11], or elbow [12]). In these models, the line segments are considered as linear springs; this is straightforward, but has several limitations, such as the inability to describe complex geometry or to predict nonuniform stresses and strains.…”
Section: Introductionmentioning
confidence: 99%
“…A common approach here is to employ single or multiple line segments connecting bones (see e.g. for the knee [9,10], forearm [11], or elbow [12]). In these models, the line segments are considered as linear springs; this is straightforward, but has several limitations, such as the inability to describe complex geometry or to predict nonuniform stresses and strains.…”
Section: Introductionmentioning
confidence: 99%